Prospective study on diagnostic efficacy of targeted NGS vs. traditional testing for respiratory infections in myelosuppressed hematology patients - Li, Chen; Wu, Jing; Feng, Yuhu (Frontiers in Medicine, 2025)
BackgroundRespiratory tract infections are a significant complication in myelosuppressed hematological patients, especially those with myelosuppression. Traditional microbiological testing methods often show limitations in sensitivity, turnaround time, and cost, making them less effective in this vulnerable population. This study aimed to evaluate the diagnostic efficacy of targeted next-generation sequencing (tNGS) compared to traditional microbiological testing methods (TMT) in detecting respiratory infections among myelosuppressed hematological patients.MethodsThis prospective study included 20 patients aged ≥15 years with myelosuppressed hematological disease and respiratory infection, admitted to the hematology department of Fuyang People’s Hospital between January and May 2024. Eligible patients underwent both 198-pathogen respiratory tract infection targeted NGS panel (198-pathogen RTI tNGS panel) and TMT. Exclusion criteria included refusal of tNGS or incomplete sputum collection. The diagnostic performance of 198-pathogen RTI tNGS panel was assessed against TMT, with diagnoses confirmed by three independent hematology experts. The study adhered to ethical guidelines and obtained informed consent from all participants.ResultstNGS demonstrated a 100% pathogen detection rate compared to 40% with traditional testing (p < 0.001). It identified a broader spectrum of pathogens, including bacteria, viruses, and fungi, many of which were missed by TMT. The most common pathogens isolated in the clinical specimens detected by TMT was Epstein–Barr virus. The most common pathogens isolated in the clinical specimens detected by 198-pathogen RTI tNGS was novel coronavirus, human respiratory syncytial virus type B, and influenza A virus. The sensitivity of tNGS was 94.74%, with a positive predictive value of 100%. The turnaround time for tNGS was significantly shorter, averaging 24 h, enabling quicker adjustments to antimicrobial therapy. In 75% of cases, the tNGS results directly influenced changes in treatment regimens, improving clinical outcomes.ConclusiontNGS offers superior sensitivity, a broader pathogen detection range, and a faster turnaround time compared to traditional microbiological testing methods. It provides a practical and efficient diagnostic option for respiratory infections in hematological patients, particularly those unable to undergo invasive procedures such as bronchoalveolar lavage. The use of tNGS may enhance clinical management and improve patient outcomes in this population.